Development of a rapid GC-FID method to simultaneously determine triethylamine, diisopropylamine, and 1,1,3,3-tetramethylguanidine residues in an active pharmaceutical ingredient - Minshan Shou; Haixiao Qiu (Elsevier, 2021)
A rapid GC-FID method was developed to simultaneously determine residual levels of triethylamine (TEA), 1,1,3,3-tetramethylguanidine (TMG), and diisopropylamine (DIPA) in the synthetic route of an active pharmaceutical ingredient (API). Due to the severe absorption of amines on GC stationary phases, GC columns with various stationary phases were evaluated for optimal peak shape and reproducibility. The final conditions used the Agilent CP-Volamine column to resolve the three amines in 12 min. Various inlet liners were also screened to further improve the sensitivity of the analysis. The Restek Siltek® liner was selected to achieve the desired detectability for the method. The quantitation limits were 4, 3, and 4 μg/mL for TEA, DIPA, and TMG in the presence of API, respectively. All three amines showed good linearity (r > 0.999) and recoveries (> 90%) over the concentration range of 3 to 16 μg/mL. The testing of residual amines was initially performed at the penultimate stage of the synthesis. However, this work demonstrates that TMG can act as a proton sponge to react with salicylic acid, the counter ion of the penultimate, to form a volatile component that elutes at a different retention time. Consequently, in the final method, these three amines were monitored in the final API to circumvent the matrix interference. Key parameters of the method were qualified per method validation requirements in ICH guidelines. The method was successfully applied for batch testing during development and implemented as an in-process control procedure at manufacturing sites.